2023
DOI: 10.3390/jmse11020339
|View full text |Cite
|
Sign up to set email alerts
|

Sea-Surface Small Target Detection Based on Four Features Extracted by FAST Algorithm

Abstract: On account of current algorithm and parameter design difficulties and low detection accuracy in feature extractions of small target detections in sea clutter environment, this paper proposes a correspondingly improved four feature extraction method by FAST. After the short-time Fourier transform is applied, a time–frequency distribution spectrogram of original data is generated. Candidate feature points (CFP) are first extracted by FAST algorithm, and then a four-feature extraction is implemented with FAST and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Relevant studies are shown in Table 1. Difficulties in feature extraction [7] As deep learning research continues to advance, convolutional neural networks [8,9] have been used to classify sea clutter and noise. Through convolutional neural networks and feature perception technologies, researchers have proposed various image-based encoding methods to enhance the accuracy and generalization capability of target detection, as shown in Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies are shown in Table 1. Difficulties in feature extraction [7] As deep learning research continues to advance, convolutional neural networks [8,9] have been used to classify sea clutter and noise. Through convolutional neural networks and feature perception technologies, researchers have proposed various image-based encoding methods to enhance the accuracy and generalization capability of target detection, as shown in Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…Existing applications of the wave bathymetry method through optical remote sensing (WBM-ORS) wave depth measurement method have shown that both the Fast Fourier Transform (FFT) and SPM methods yield accurate depth measurement through wavelength inversion [40,50]. However, the FFT method still has limitations in certain scenarios [51,52]. Shen et al conducted simulation research and found that the FFT method requires a specific image resolution and subimage size, with the subimage length being 4-8 times the wavelength [53].…”
Section: Introductionmentioning
confidence: 99%